Evaluation of senescent cells in intervertebral discs by lipofuscin staining. (October 2021) - Veroutis, Dimitris; Kouroumalis, Anastasios; Lagopati, Nefeli; Polyzou, Aikaterini; Chamilos, Christos; Papadodima, Stavroula; Evangelou, Konstantinos; Gorgoulis, Vassilis G.; Kletsas, Dimitris
Highlights: Lipofuscin staining proved to be a robust marker of senescent IVD cells GL13 staining can be used in FFPE intervertebral discs GL13 staining confirms the increased number of senescent cells in aged IVDs Abstract: Intervertebral disc (IVD) degeneration is considered an important contributor of low back pain, a major age-related disease. Interestingly, an unprecedented high number of senescent cells has been reported in aged and degenerated IVDs, most probably affecting tissue homeostasis. In previous studies classical markers of cellular senescence have been used, such as SA-β-gal staining or p16 Ink4a expression. Aim of the presented study was a re-evaluation of the number of senescent IVD cells by using a newly established staining procedure for lipofuscin, based on a Sudan Black-B analogue (GL13), which can be used in fresh, as well as in fixed and embedded tissues. In cultures of senescent rat and human IVD cells both SA-β-gal and GL13 gave similar percentages of senescent cells. Similarly, in fresh tissues from old rats the ratios of senescent cells were high with both detection procedures. Finally, in formalin-fixed and paraffin-embedded tissues from humans, a significant increased number of GL13-positive cells was found in herniated tissues, as compared to apparently normal ones, while similar numbers of p16 Ink4a -positive cells were observed. These data confirm the significantly enhanced number of senescent cells in aged and degenerated IVDs, most probably contributing to the degeneration of this tissue.